High-performance electrochemical sensor based on Pt-Ag@Cu-BDC MOF composite modified glassy carbon electrode for detection of imidacloprid in citrus juice and water samples - Fariba Hasani; Jahan Bakhsh Raoof; Reza Ojani; Milad Ghani (Heliyon)
The key factor to improve the sensitivity of electrochemical sensors for direct detection, is the introduction of new nanomaterials with enhanced catalytic properties. Accordingly, we prepared Pt-Ag@Cu-metal organic framework (MOF) as a novel nanocomposite to construct a sensitive electrochemical sensor for voltammetric determination of imidacloprid (IMI). The copper benzene-1,4-dicarboxylate framework (Cu-BDC MOF) was used as support for bearing the metal nanoparticles (NPs) including Ag and Pt. First, Ag NPs were incorporated into Cu-BDC MOF and then Pt NPs were substitute through galvanic replacement reaction between Ag NPs and Pt ions. The Pt-Ag@Cu-BDC MOF as a novel nanocomposite was utilized as a modifier to decorate glassy carbon (GC) electrode. The excellent conductivity, hierarchical and micro-mesoporous structure of Pt-Ag@Cu-BDC MOF and the synergistic effect between Ag and Pt nanoparticles were beneficial for fast electron transfer required for IMI reduction. At the Pt-Ag@Cu-BDC MOF/GCE, reduction potential of IMI was greatly shifted to positive value and the electrochemical signal increased significantly. The prepared sensor exhibited wide linear range (5 nM-10000 nM), low detection limit (1.5 nM) and high sensitivity towards IMI detection. This sensor was successfully applied for detection of IMI in citrus juice and water samples with good recoveries (92–106 %, RSD ≤4 %).